Effect of Selected Essential Oils on Brown Recluse Spider Control - Kragelund, Ashley; Ewing, Robert; Whitworth, Jeff (My University, 2018)
Loxosceles reclusa isconsidered a pest throughout its range in the US due mostly to the effects of its venomous bite (Sandidge and Hopwood, 2005). Management techniques include the use of pesticides to target this dangerous synanthropic organism. Essential oils, commonly used for various health benefits, have been previously used as a method of pest control (Koulet al, 2008). Studies have shown varying results when tested on different insects and pests (Regnault-Roger et al, 2011). Their effect on L. reclusa is still undetermined. Thus, we tested the potential of essential oils as an effective method of control for L. reclusa. Results from our experiment indicated that the selected essential oils had a varied effect with overall low mortality.
Keywords: Fall 2018